PENGARUH AUDIT MANAJEMEN SUMBER DAYA MANUSIA TERHADAP PENINGKATAN KINERJA KARYAWAN PADA PT PLN (PERSERO) RAYON BLAMBANGAN UMPU PROVINSI LAMPUNG - . Sugiharto (Universitas Tridinanti, 2020)
ABSTRACK PT PLN persero blambangan umpu, Lampung province, is a state-owned company that operates in the electricity sector, from outside operating power plants to transmitting to the public for all Indonesian people, showing a decline in employee performance. This problem have a lot of existence; delay in work, ineffective internal control and the implementation of human resource management audits that are not optimal and its run into the errors in the operation of power plants and transmissions that are not yet optimal. This is partly influenced by the human resource management audits. The population and sample in this study were as many as 40 employees, all of whom were made into the population, with the type and design of the research used exploratory and causality with associative problem formulations. Based on the results of research, human resource management audits have an effect on employee performance, from the results of the t test, the significance is smaller than Alpha 0.05, which means that Ho is rejected and Ha is Accepted. A correlation coefficient which states the closeness of the relationship is strong and positive of 0.536. With a determination coefficient of 28.7%. The conclusion of this study states tell that the hypothesis of human resource management audits affect employee performance is acceptable Keywords : Human Resource Management Audits, Employee Performance